หอสมุดกลาง สถาบันวิทยบริการ จุฬาลงกรณ์มหาวิทยาลัย - ขนิษฐ ตัณฑวิรัตน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The history of the Central Library can be traced back to 1910, when the Civil Servant School was established. The Library was formally set up as the University Central Library of Chulalongkorn University on March 26, 1916. The administration and operation of the Library are described by dividing into four divisions: (1) Administration, (2) Technical Work, (3) Services, and (4) Special Services. The function and responsibility of the Library are to provide and acquire books both in Thai and foreign languages of various field of specialization with a view to obtaining the required information necessary for research study. Apart from these, the Library is collecting rare books on Thailand, including documents, announcements, and records concerning the University. The Library is also compiling research tools such as union catalogs and union list of serials. To provide information services to students and researchers, it is necessary to have Reference Service, Bibliography Compilation, Thesis Index, Publication, Duplicating Service, and Reserve Book etc. The problems of underachievement of the Library in the past are discussed. At present, the Central Library and the other two formerly autonomous organizations, namely, Thailand Information Center and the University-Audio-Visual Center, have been made three component parts of the newly established Institute of Academic Resource Organization chart of the Central Library and statistics of work accomplishments, F.Y. 1978 are included.